Effect of the polymer "solid rain” and irrigation frequencies in the performance of yellow hard corn, Lambayeque - Orbegoso Navarro, Luis Alberto (2019)
The objectiveswere: a) to determine the best response of the YellowCorn(Mega Hybrid) crop to four doses of potassium polyacrylate (40, 60, 80 and 100 kg / ha); and b) determine thewater requirement of the Yellow Corn (Mega Hybrid) crop, according to different gravity irrigation frequencies. Using the SPSS Ver.22 statistical package, variance tests and Duncan averages testswere performed to determine the effect of treatments, resulting in a signicant difference between the Irrigation Frequencies among them, ie but one is different; that at the dose level of the gel there is no significant difference, ie, at any dose applied, the results in the performance of "Mega Hybrid” Hard Yellow Corn are quite even. The best answer turns out to be the T2 Treatment (60 kg / ha), for the Irrigation Frequency of 30 days. The maximum and minimum water requirements were 6847, 30 and 2239, 00 m3 / ha and the yields were: 8824 and 12708 kg / ha for the irrigation frequencies: T0 and T4, respectively. The water used has been of class S4-C1, with high salt content and low risk of sodium.